Sustainability in the Textile Industry - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology, 2017)
This book examines in detail key aspects of sustainability in the textile industry, especially environmental, social and economic sustainability in the textiles and clothing sector. It highlights the various faces and facets of sustainability and their implications for textiles and the clothing sector.